Silver-loaded poly(vinyl alcohol)/polycaprolactone polymer scaffold as a biocompatible antibacterial system - Vilamová, Zuzana; Šimonová, Zuzana; Bednář, Jiří; Mikeš, Petr; Cieslar, Miroslav; Svoboda, Ladislav; Dvorský, Richard; Rosenbergová, Kateřina; Kratošová, Gabriela (Scientific reports, 2024)
A chronic nonhealing wound poses a significant risk for infection and subsequent health complications, potentially endangering the patient's well-being. Therefore, effective wound dressings must meet several crucial criteria, including: (1) eliminating bacterial pathogen growth within the wound, (2) forming a barrier against airborne microbes, (3) promoting cell proliferation, (4) facilitating tissue repair. In this study, we synthesized 8 ± 3 nm Ag NP with maleic acid and incorporated them into an electrospun polycaprolactone (PCL) matrix with 1.6 and 3.4 µm fiber sizes. The Ag NPs were anchored to the matrix via electrospraying water-soluble poly(vinyl) alcohol (PVA), reducing the average sphere size from 750 to 610 nm in the presence of Ag NPs. Increasing the electrospraying time of Ag NP-treated PVA spheres demonstrated a more pronounced antibacterial effect. The resultant silver-based material exhibited 100% inhibition of gram-negative Escherichia coli and gram-positive Staphylococcus aureus growth within 6 h while showing non-cytotoxic effects on the Vero cell line. We mainly discuss the preparation method aspects of the membrane, its antibacterial properties, and cytotoxicity, suggesting that combining these processes holds promise for various medical applications.
Keywords: Microbial Sensitivity Tests; Chlorocebus aethiops; Staphylococcus aureus; Cytotoxicity; Polyesters; Electro-spraying; Vero buňky; mikrobiální testy citlivosti; Tissue Scaffolds; Escherichia coli; antibakteriální látky; zvířata; Polyvinyl Alcohol; Silver; kovové nanočástice; Antimicrobial properties; polyvinylalkohol; Cercopithecus aethiops; Biocompatible Materials; polyestery; tkáňové podpůrné struktury; Anti-Bacterial Agents; stříbro; biokompatibilní materiály; Animals; Wound healing; Silver nanoparticle; Metal Nanoparticles; Vero Cells